Corrosion protection properties of tetraphenylethylene-based inhibitors toward carbon steel in acidic medium. Issue 12 (14th March 2023) - Chen, Yumeng; An, Yiming; Ma, Jing; Zhang, Zhihua; Qiao, Fulin; Lei, Xue; Sun, Fei; Wang, Chunlu; Gao, Song; Zhao, Yue; Wang, Jinhua; Fu, Xiaoping; et al.
Abstract : Four corrosion inhibitors containing tetraphenylethylene were synthesized and proved to protect carbon steel effectively in acidic medium. Abstract : Four novel corrosion inhibitors (1, 2, 3 and 4 ) integrating different tetraphenylethylene (TPE) cations and thiocyanate (SCN − ) anions were developed. Weight-loss and electrochemical measurements were employed to assess their protective properties toward carbon steel in 0.5 M H2 SO4, revealing them as effective corrosion inhibitors in the order of 3 > 4 > 2 > 1, with the inhibition efficiencies of 2, 3 and 4 all exceeding 97%. The inhibitory effect could be attributed to hard and soft acids and bases theory and the synergistic effect of the charged ingredients. The efficiency trend of the corrosion inhibition, as well as inhibition mechanism, was verified by multi-scaled theoretical simulations combined with grand canonical Monte Carlo and molecular dynamic methods.